PANDORA-seq expands the repertoire of regulatory small RNAs by overcoming RNA modifications - Shi, Junchao; Zhang, Yunfang; Tan, Dongmei; Zhang, Xudong; Yan, Menghong; Zhang, Ying; Franklin, Reuben; Shahbazi, Marta; Mackinlay, Kirsty; Liu, Shichao; Kuhle, Bernhard; James, Emma R.; et al. (Nature cell biology, 2021)
Although high-throughput RNA sequencing (RNA-seq) has greatly advanced small non-coding RNA (sncRNA) discovery, the currently widely used complementary DNA library construction protocol generates biased sequencing results. This is partially due to RNA modifications that interfere with adapter ligation and reverse transcription processes, which prevent the detection of sncRNAs bearing these modifications. Here, we present PANDORA-seq (panoramic RNA display by overcoming RNA modification aborted sequencing), employing a combinatorial enzymatic treatment to remove key RNA modifications that block adapter ligation and reverse transcription. PANDORA-seq identified abundant modified sncRNAs—mostly transfer RNA-derived small RNAs (tsRNAs) and ribosomal RNA-derived small RNAs (rsRNAs)—that were previously undetected, exhibiting tissue-specific expression across mouse brain, liver, spleen and sperm, as well as cell-specific expression across embryonic stem cells (ESCs) and HeLa cells. Using PANDORA-seq, we revealed unprecedented landscapes of microRNA, tsRNA and rsRNA dynamics during the generation of induced pluripotent stem cells. Importantly, tsRNAs and rsRNAs that are downregulated during somatic cell reprogramming impact cellular translation in ESCs, suggesting a role in lineage differentiation. Shi et al. profiled small non-coding RNAs (sncRNAs) through PANDORA-seq, which identified tissue-specific transfer RNA- and ribosomal RNA-derived small RNAs, as well as sncRNAs, with dynamic changes during induced pluripotent stem cell reprogramming.